Commitment Systems in Cross‐boundary Work. (1st May 2022) - van Rossenberg, Yvonne G. T.; Swart, Juani A.; Yalabik, Zeynep Y.; Cross, David; Kinnie, Nicholas
Abstract: Work increasingly takes place across organizational boundaries. This has implications for workers' commitments to a plethora of targets, including the organization and the client, as well as for the conflicting nature of the interrelation between these commitments. In this paper, we draw on commitment system theory (CST), which views commitment as a malleable and interconnected system. Using a pragmatic abductive and quantitative discovery approach, we distinguish and develop commitment systems to consist of strength, including the multiple targets and types of commitment, as well as interaction between commitments, including coupling and nature . In particular, we develop a theoretical understanding of the nature dimension by identifying two target‐neutral types of conflict and one context‐ and target‐specific type of conflict. Three commitment systems are identified: ' balanced system ', ' conflicting system ', and ' detached system '. Furthermore, we provide insights into how job demands resources and contextual job aspects influence membership of these commitment systems. This paper is the first to empirically explore commitment as a system, and it advances the theoretical understanding of commitment systems in a cross‐boundary space. Our study discusses the theoretical, methodological and practical implications for cross‐boundary organizations that compete with their clients for the commitment of their employees.